Sistem Informasi Rental Mobil Pada Regulator Rent Car - Satmoto, Bambang; Wulan, Rayung; Saputra, Aswin (CV. Hawari, 2023)
Car rental is an activity of renting a vehicle in the form of a car with the terms and conditions determined by the rental party. Every time a rental transaction is made, the Car Rent Regulator always records data on each customer and transactions made in writing. In addition, the rental party also cannot determine the choice of the best available car. This study aims to build an information system that can be applied to Car Rent Regulators, so that the transaction process can be carried out more quickly and reduce the risk of data damage. This system will apply the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to determine the choice of the best car available at the rental. System information is created using the Java programming language and MySQL as a database. In designing the system, the Unified Modeling Language (UML) model is used to determine the structure and processes that occur in the system. The results of this study can facilitate and improve admin performance in conducting rental transactions, and calculations using the TOPSIS information system method can determine the choice of the best available car by entering values in the specified criteria. The results of calculations using the TOPSIS method show that the Avanza car is the best car choice available for rental.